Theoretical development of discrete-modulated continuous-variable quantum key distribution - Liu, Wen-Bo; Li, Chen-Long; Liu, Zhi-Ping; Zhou, Min-Gang; Yin, Hua-Lei; Chen, Zeng-Bing (Frontiers in Quantum Science and Technology, 2022)
Continuous-variable quantum key distribution offers simple, stable and easy-to-implement key distribution systems. The discrete modulation scheme further reduces the technical difficulty. The main regret is that the security of discrete modulation schemes has not been sufficiently demonstrated. Schemes with different signal state distributions use various physical conditions to obtain the key rate formula, resulting in different security levels, computation complexities and implementation difficulties. Therefore, a relatively systematic and logically consistent security proof against most general attacks is worth exploring. On the other hand, extending the discrete modulation scheme and its variants to different applications, such as satellite-to-earth communication, can further activate and advance this field. Here, we briefly review the achievements that have been made in discrete-modulated continuous-variable quantum key distribution, and openly discuss some issues worthy of further research.